Fede religiosa versus pluralismo: un intervento educativo - Colicchi, Enza (Studi sulla Formazione/Open Journal of Education, 2012)
Religion, today, is in a condition, theoretical and practical, of pluralism. The religious view is based on encounter and dialogue, against every dogmatism and is based on democratic debate about respect and value of difference. To “form” by education.